(untitled) (Research, Society and Development, 2021)
The debates related to inclusive education originated a few decades ago, but suffering the strong influence of a segregational culture that excluded people (a phenomenon historically built by various prejudices) for not belonging to a common standard. Thus, the main objective of this research is to investigate the status of the inclusion of the Visually Impaired Person - VDP in the educational system and the specific objectives are: to investigate the possible effective teaching-learning strategies; how is the initial and continuing education of teachers and investigate the perception of the blind student to the reality of this inclusive process. For this, a qualitative study of descriptive nature was carried out, through previously chosen key words and some inclusion and exclusion criteria to be applied in databases and renowned periodicals. The results of the research revealed that it is important to invest in the initial and continuing education of teachers, in order to sensitize and encourage them to a reflective work in order to recognize the peculiarities of the blind student and to work in a multiprofessional way, since the inclusive process is not far from being effective. It was also found that there are several methodologies and strategies in the attempt to include the PDV at school. Such manifestations are basic assumptions that make the teaching-learning process more accessible, but not yet fully inclusive. Thus, there is much to be done before we can consider the PDV teaching-learning process inclusive.